Advancing the next-generation of global food system scenarios: a critical review of existing narratives - Gupta, Bhawana; Zurek, Monika; Woodhill, Jim; Ingram, John S. I. (Frontiers in Sustainable Food Systems, 2025)
The recent global crises suggest that historic and current trends in the food system become less relevant when frequently disrupted by unexpected events, such as trade conflicts, the rise of inward-looking, right-wing governments, or another global pandemic. In the face of food insecurity, the foresight community is more strongly emphasizing the need to consider various plausible scenarios when preparing critical strategies within and around the intricate global food system. As scenarios have been developed for many decades, two questions arise: how is the food system community engaging in scenario planning, particularly given the urgent need for transformation coupled with current poly-crisis; and what is needed to enhance the process of scenario planning for the global food system? Therefore, the purpose of this paper is to critically review existing scenarios on global food systems, published by key organizations and authors in the last eight years, to identify common themes of plausible food system futures, the key uncertainties and emerging radical ideas. The paper is based on an inductive clustering framework that offers a method for evaluating the potential outcomes of varying governance structures and policy actions within scenario clusters across key dimensions—health and nutrition, livelihoods and equity, and climate and environment. The critical analysis of the scenario clusters leads to two important findings: (i) megatrends such as shifting demography, technology and consumption patterns are often central in reviewed scenario exercises, and radical notions have not significantly evolved but have taken on new dimensions; and (ii) while factors like consumption patterns, technology, and investment influence food systems significantly, governance structures play a crucial role in shaping the environment for these factors to interact. This underscores the importance of adaptive policymaking in responding to evolving uncertainties. This study provides a strong foundation for designing a next-generation global food system scenario exercise. It calls for a more ambitious, inclusive, and innovative approach for delving into a broader range of uncertainties, radical forces of change and prioritizing the interrogation of drivers related to geopolitical tensions, technological innovations, governance, social influences, and social inequalities.